Needs Assessment in Forensic Patients: A Review of Instrument Suites. Issue 3 (2nd July 2016) - Keulen-de Vos, Marije; Schepers, Klaartje
ABSTRACT: In the last few decades, the forensic literature has been dominated by violence risk and instruments that assess risk for violent and criminal behavior. Typically, these instruments are guided by the theoretical risk-need-responsivity model. According to this model, criminogenic needs are the cornerstone for forensic treatment. Criminogenic and general needs, such as mental health, quality of life, and social factors, are important for care planning in offenders because unmet needs can have significant implications for offenders' future violence risk. However, needs assessment in forensic mental health services is still underdeveloped when compared to the long tradition of needs assessment in general psychiatric mental health services. Recently, internationally validated instruments that measure needs in psychiatric populations, such as the Camberwell Assessment of Need (CAN), Health of the Nations Outcome Scales (HoNOS), and international Resident Assessment Instrument (interRAI) have been adapted for forensic purposes. In this article, we review the forensic adaptations of these and potential other instruments including its psychometric evidence base.